PERILAKU PASANGAN YANG BARU MENIKAH DALAM MENUNAIKAN ZAKAT FITRAH (UIN Sunan Kudus, 2017)
Zakat fitrah is a number of treasures that must be fulfilled by any person, sentient, and baligh, every person who is paid by it in order with certain conditions. The purpose of this research is to know the behavior of newly married couples in district Five Clans in some elements, namely command in addressing behavior Zakah, fitrah zakat fitrah in calculating the behavior that will be fulfilled, behavior in choosing the form of zakat which ended behavior in choosing media distribution of zakat, and behavior in choosing the time of zakat. This type of research is a field research with quantitative analysis approach to qualitative and descriptive. The data collected through questionnaires. The results of this research in the form of percentage of respondents answer appropriate behavior indicators chosen by the respondent. From research conducted there is variation in the answers of the respondents on each indicator behavior with varying percentages.